2016
DOI: 10.1055/s-0036-1572432
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Nasopharyngeal Colonization with Group B Streptococcus and its Association with Clinical Sepsis

Abstract: Objective This study aims to determine whether nasopharyngeal (NP) colonization with group B streptococcus (GBS) is associated with early-onset clinical sepsis within 72 hours of birth, prolonged antibiotic duration, longer neonatal intensive care unit (NICU) stay, and delay in tolerating full feeds among neonates ≥ 35 weeks gestation. Study Design A retrospective cohort study of 192 NICU neonates admitted for sepsis evaluation. Based on their GBS colonization status, the mother-neonate pairs were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…GBS is part of the normal gut and genital microbiota, and though GBS nasopharyngeal colonization has been reported, it is poorly understood [13, 17]; no clearance protocol has been shown to be reliable. Therefore, reinforcement of hand and environmental hygiene seemed the most suitable option to manage the outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…GBS is part of the normal gut and genital microbiota, and though GBS nasopharyngeal colonization has been reported, it is poorly understood [13, 17]; no clearance protocol has been shown to be reliable. Therefore, reinforcement of hand and environmental hygiene seemed the most suitable option to manage the outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated that nasopharyngeal culture has the highest positive predictive value among cultures of other body surfaces (25,26). One study showed that the probability of clinical sepsis in colonized infants was significantly higher than that in non-colonized infants (27).…”
Section: Discussionmentioning
confidence: 99%
“…Out of these isolates, 37.5% were resistant to ampicillin, and 100% were sensitive to vancomycin. The prevalence of CoNS in the development of early-onset sepsis ranges from 22.5 to 72.7% (27)(28)(29). This may be partly due to contamination during sampling for culture or due to the widespread presence of this group of bacteria on human skin.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, another study stated that nasopharyngeal cultures positive for GBS in newborns can be used as an indicator for diagnosis and management of presumed GBS sepsis. 15 Variations on bacterial colonization in nasopharynx represent local bacterial colonization. Bacteria found in the nasopharynx of our subjects were opportunistic, with a predominance of Gram-negative bacteria, including Alcaligenes faecalis.…”
Section: Discussionmentioning
confidence: 99%